Antiplatelet therapy in secondary prevention of ischemic stroke - V. A. Parfyonov; S. V. Verbitskaya (Медицинский совет, 2015)
The article is a review of literature on antiplatelet (antiagregant) therapy in the secondary prevention of ischemic stroke (IS). The latest guidelines (2014) from the American Heart Association and stroke experts are discussed. The efficacy of acetylsalicylic acid (ASA), extended-release dipyridamole in combination with ASA, clopidogrel, a slight superiority of extended-release dipyridamole in combination with ASA and of clopidogrel over ASA in reducing the risk of recurrent ischemic events. The possibility of using clopidogrel in combination with ASA in patients after transient ischemic attack or small IS in the first 90 days of illness is considered. The problems of antiplatelet therapy in clinical practice are analyzed. The authors note that clinical application of the global guidelines for the secondary prevention of IS could reduce the incidence of stroke and the associated mortality.